Aluminum alloy hard soldering sheet and method of manufacturing the same
Patent Information
- Application Number
- CN202280058592.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-21
- Filing Date
- 2022-08-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-08-09
AI Technical Summary
[0010]然而,Mg比较容易被氧化,钎料表层的Mg与从外部进入的氧反应,容易形成MgO被膜
[0038] According to the present invention, a brazing board with excellent brazing properties when brazing aluminum materials in an inactive gas atmosphere such as nitrogen without the use of flux, and a method thereof are provided.
Smart Images

Figure BDA0004716917010000221 
Figure BDA0004716917010000231 
Figure BDA0004716917010000232
Abstract
Description
Technical Field
[0001] This invention relates to aluminum alloy brazing plates and their manufacturing methods. Background Technology
[0002] Aluminum products, such as heat exchangers and mechanical parts, consist of multiple components made of aluminum (including aluminum and aluminum alloys, the same applies below).
[0003] The aforementioned aluminum products have numerous small joints, and brazing is widely used as the joining method to form these joints. Most of these aluminum products are brazed using an aluminum material having a core and a filler metal disposed on at least one side of the core, known as a brazing board.
[0004] To braze aluminum materials (including aluminum alloys), a method is required whereby, during brazing, the oxide film covering the surface of the brazing filler metal is broken, and the molten brazing filler metal comes into contact with the material to be joined, thereby breaking the oxide film covering the surface of the material. Such methods are broadly classified into methods using flux (flux brazing) and methods involving heating in a vacuum (vacuum brazing), both of which have been put into practical use.
[0005] Flux brazing, one of these methods, involves applying flux to the surface of the intended joint, i.e., the part to be joined by brazing, and then brazing it.
[0006] However, in flux brazing, a flux coating process is required before brazing, followed by the removal of the flux and its residue after brazing. This increases the manufacturing cost of aluminum products. Furthermore, if the flux and its residue are not adequately removed after brazing, sufficient surface quality may not be achieved during subsequent surface treatments.
[0007] On the other hand, vacuum brazing is a method that involves brazing in a vacuum without applying flux to the surface of the intended joint.
[0008] However, compared to flux brazing, vacuum brazing has lower productivity and is less likely to achieve satisfactory brazing quality. Furthermore, compared to conventional brazing furnaces, vacuum brazing furnaces tend to result in higher equipment and maintenance costs.
[0009] Therefore, a so-called fluxless brazing method has been proposed, in which flux is not applied to the surface of the intended joint and brazing is performed in an inactive gas atmosphere. The brazing board used in the fluxless brazing method has at least one layer of the laminated structure containing an element that embrittles or destroys the oxide film; Mg is commonly used as this element.
[0010] However, Mg is relatively easy to oxidize. The Mg on the surface of the solder reacts with oxygen that enters from the outside, easily forming a MgO film.
[0011] Compared to Al2O3 film, this MgO film is very strong. Therefore, for brazing boards with a thick MgO film, the MgO film will not be damaged during brazing, and the molten filler metal will have difficulty wetting and spreading on the surface, thus making it difficult to achieve good brazing performance.
[0012] That is, even if the Al2O3 film on the surface of the brazing board is thin, poor brazing is still likely to occur if the MgO film is thick.
[0013] In this context, Patent Document 1 proposes an aluminum alloy brazing board for brazing in an inactive gas atmosphere without the use of flux. The aluminum alloy brazing board comprises a core material made of aluminum or an aluminum alloy and an aluminum alloy filler metal containing 4.0 to 13.0% by mass of Si covering one or both sides of the core material. By heating for brazing, oxide particles containing X atoms are formed on the surface. The volume change rate of the oxide particles relative to the oxide film before brazing heating is less than 0.99.
[0014] Furthermore, Patent Document 2 discloses a fluxless brazing method for aluminum materials. The method is characterized by using a brazing board in a non-oxidizing atmosphere with an oxygen concentration of 50 ppm or less without depressurization. The Al-Si-Mg solder of the brazing board and the component to be brazed are brought into close contact. In the contacted area, the core material and the component to be brazed are brazed together using the Al-Si-Mg solder without flux. In the brazing board, the Al-Si-Mg solder, containing 5.0–13.0% Si and 0.1–3.0% Mg by mass, coats the core material and is located on the outermost surface. The average thickness of the oxide film on the surface of the Al-Si-Mg solder before brazing is... Below, and the average film thickness of the magnesium oxide film in the oxide coating is the following.
[0015] Existing technical documents
[0016] Patent documents
[0017] Patent Document 1: Japanese Patent Application Publication No. 2019-069474
[0018] Patent Document 2: Japanese Patent Application Publication No. 2013-215797 Summary of the Invention
[0019] The problem the invention aims to solve
[0020] However, the inventors conducted research and found that, for the brazing board described in Patent Document 1, when the oxide film on the surface of the solder becomes thick, it is not possible to sufficiently destroy the oxide film, and the molten solder does not sufficiently wet and spread on the surface. As a result, the desired new surface cannot be exposed, and poor brazing is easily produced.
[0021] Patent document 1 also describes a method to make the oxide film on the surface of the solder easier to destroy by setting the thickness of the oxide film to less than 30 nm. However, the degree of difficulty in destroying the oxide film varies depending on the elements constituting it. Therefore, it is difficult to suppress the occurrence of poor hard soldering by simply controlling the thickness of the oxide film.
[0022] In addition, the inventors conducted research and found that, for the brazing board described in Patent Document 2, even if the thickness of the MgO film before brazing heating is relatively thin, the MgO film will still form and grow during brazing heating because the solder contains Mg.
[0023] That is, it was discovered that, for the brazing board described in Patent Document 2, when the solder melts, since the oxide film has already formed to a relatively thick thickness, the oxide film is not destroyed, and the molten solder cannot wet and spread on the surface, which leads to a reduction in brazing performance.
[0024] Under such circumstances, the object of the present invention is to provide a brazing board and a method thereof that can exhibit excellent brazing properties when brazing aluminum materials in an inactive gas atmosphere such as nitrogen without the use of flux.
[0025] Solution for solving the problem
[0026] To solve the aforementioned technical problems, the inventors conducted repeated and in-depth research and discovered that the above technical problems can be solved using the following aluminum alloy brazing board. Based on this insight, the inventors completed the present invention. This aluminum alloy brazing board is used for brazing in an inactive gas atmosphere. The aluminum alloy brazing board has a core material and a filler metal covering one or both sides of the core material. The core material comprises an aluminum alloy containing 0.10 to 0.50% by mass of Mg and the balance being aluminum and unavoidable impurities. The filler metal comprises an aluminum alloy containing 6.00 to 13.00% by mass of Si and the Mg content is limited to less than 0.05% by mass, the balance being aluminum and unavoidable impurities. The Mg integral value from the surface of the filler metal to a depth of 30 nm is less than 150 atm% × nm.
[0027] That is, the present invention provides (1) an aluminum alloy brazing board for brazing in an inactive gas atmosphere or in a vacuum, characterized in that the aluminum alloy brazing board has a core material and a solder covering one or both sides of the core material, the core material comprising an aluminum alloy containing 0.10 to 0.50% by mass of Mg and the balance comprising aluminum and unavoidable impurities, the solder comprising an aluminum alloy containing 6.00 to 13.00% by mass of Si and the Mg content is limited to less than 0.05% by mass, the balance comprising aluminum and unavoidable impurities, and the Mg integral value from the surface of the solder to a depth of 30 nm is less than 150 atm% × nm.
[0028] (2) The aluminum alloy brazing board according to (1) above is characterized in that the brazing filler metal further contains less than 1.00% by mass of Bi.
[0029] (3) The aluminum alloy brazing board according to (1) or (2) above is characterized in that the core material further contains one or more of the following elements: Fe less than 0.70% by mass, Si less than 0.70% by mass, Mn less than 1.60% by mass, and Cu less than 0.50% by mass.
[0030] (4) The aluminum alloy brazing board according to any one of (1) to (3) above, characterized in that the core material further contains less than 3.00% by mass of Zn.
[0031] (5) The aluminum alloy brazing board according to any one of (1) to (4) above, characterized in that the surface of the aluminum alloy brazing board is etched by acid.
[0032] (6) A method for manufacturing an aluminum alloy brazing board, comprising the method for manufacturing an aluminum alloy brazing board as described in any one of (1) to (5) above, characterized in that the aluminum alloy brazing board is manufactured by subjecting a laminate formed by stacking a core material ingot and a brazing filler ingot on one or both sides of the core material ingot to at least hot working, cold working, and at least one annealing treatment selected from at least one intermediate annealing between cold working rolling passes and a final annealing after the last cold working pass, wherein during manufacturing,
[0033] So that the value of the diffusion amount D, expressed by the following equation (I), becomes 7.0 × 10⁻⁶. -10 m 2 The heating process for annealing is performed in the following manner, selecting from the intermediate annealing between the cold rolling passes and the final annealing after the last cold working pass, for one or more annealing treatments.
[0034] D=ΣD0·exp(-Q / (RTn))·Δtn (I)
[0035] (In the formula, Tn is the heating temperature (K) in each minute time interval when the total heating time (seconds) of the intermediate annealing and final annealing is divided into minute time intervals Δtn (seconds), D0 = 1.24 × 10 -4 (m 2 / s), Q=130(kJ / mol), R=8.3145(J / (mol·K))).
[0036] (7) The method for manufacturing an aluminum alloy brazing board according to (6) above is characterized in that the intermediate annealing or final annealing is performed while the brazing filler metal is rolled into an ingot with a thickness of 10 μm to 50 μm.
[0037] The effects of the invention
[0038] According to the present invention, a brazing board with excellent brazing properties when brazing aluminum materials in an inactive gas atmosphere such as nitrogen without the use of flux, and a method thereof are provided. Attached Figure Description
[0039] Figure 1 (a) is a graph showing the relationship between Mg concentration and the distance (μm) from the surface of the solder that makes up the aluminum alloy brazing board. Figure 1 (b) is Figure 1 A magnified view of the portion shown by the dashed line in (a).
[0040] Figure 2 This is a schematic diagram illustrating the microchip test specimens fabricated in the embodiments and comparative examples of the present invention. Detailed Implementation
[0041] The aluminum alloy brazing board of the present invention is used for brazing in an inactive gas atmosphere. The board is characterized in that it has a core material and a filler metal covering one or both sides of the core material. The core material comprises an aluminum alloy containing 0.10 to 0.50% by mass of Mg, with the balance being aluminum and unavoidable impurities. The filler metal comprises an aluminum alloy containing 6.00 to 13.00% by mass of Si, with the Mg content limited to less than 0.05% by mass, the balance being aluminum and unavoidable impurities. The integral value of Mg from the surface of the filler metal to a depth of 30 nm is less than 150 atm% × nm.
[0042] First, the aluminum alloy brazing board of the present invention will be described.
[0043] The aluminum alloy brazing board of the present invention has a core material and a brazing filler metal covering one side (any one main surface) or both sides (both main surfaces) of the core material.
[0044] In the aluminum alloy brazing board of the present invention, the core material comprises an aluminum alloy containing 0.10 to 0.50% by mass of Mg, with the balance being aluminum and unavoidable impurities.
[0045] In the aluminum alloy brazing board of the present invention, the core material contains Mg.
[0046] During the brazing process, the Mg contained in the core material gradually diffuses into the brazing filler metal. As the brazing filler metal begins to melt (specifically, the partial melting of the Al-Si-Mg ternary eutectic), the Mg contained in the core material rapidly diffuses toward the surface of the brazing filler metal, which can easily embrittle and destroy the aluminum oxide film covering the surface of the brazing filler metal.
[0047] Most of the Mg mentioned above is not supplied by the solder, but by the core material. Therefore, it is possible to suppress the formation of MgO on the surface of the solder and to prevent the aluminum oxide film covering the surface of the solder from becoming brittle.
[0048] In addition, Mg is dissolved in the matrix and the strength of the material is improved through solid solution strengthening.
[0049] The Mg content in the core material is 0.10–0.50% by mass, preferably 0.10–0.45% by mass, and more preferably 0.15–0.40% by mass.
[0050] By keeping the Mg content in the core material within the above range, Mg can diffuse and dissolve into the brazing filler metal in sufficient quantity, thereby embrittlement of the aluminum oxide film on the surface of the brazing filler metal. Furthermore, it can suppress the decrease in the solidus temperature (melting point) of the core material and inhibit the melting of the core material during brazing.
[0051] In the aluminum alloy brazing board of the present invention, the core material may also contain Fe.
[0052] When the core material contains Fe, the Fe content in the core material is preferably 0.70% by mass or less, more preferably 0.05 to 0.50% by mass, and even more preferably 0.10 to 0.40% by mass.
[0053] By keeping the Fe content in the core material below 0.70% by mass, it is possible to easily suppress the reduction in corrosion resistance and the formation of coarse crystals, and to easily achieve the desired strength enhancement effect by forming intermetallic compounds with other metallic elements.
[0054] In the aluminum alloy brazing board of the present invention, the core material may also contain Si.
[0055] When the core material contains Si, the Si content in the core material is preferably 0.70% by mass or less, more preferably 0.10 to 0.65% by mass, and even more preferably 0.20 to 0.60% by mass.
[0056] By keeping the Si content in the core material within the above range, local melting caused by the decrease in the melting point of the core material can be easily suppressed, and the strength of the core material can be easily improved through solid solution strengthening and fine precipitation strengthening of intermetallic compounds.
[0057] In the aluminum alloy brazing board of the present invention, the core material may also contain Mn.
[0058] When the core material contains Mn, the Mn content in the core material is preferably 1.60% by mass or less, more preferably 0.40 to 1.60% by mass, and even more preferably 0.60 to 1.50% by mass.
[0059] By keeping the Mn content in the core material within the above range, it is possible to easily suppress the reduction in rollability caused by the formation of coarse crystals during casting, easily improve the strength of the core material, and easily improve its corrosion resistance by adjusting the potential of the core material.
[0060] In the aluminum alloy brazing board of the present invention, the core material may also contain Cu.
[0061] When the core material contains Cu, the Cu content in the core material is preferably 0.50% by mass or less, more preferably 0.05 to 0.45% by mass, and even more preferably 0.10 to 0.40% by mass.
[0062] By keeping the Cu content in the core material within the above-mentioned range, the strength of the core material can be easily improved by suppressing local melting caused by the decrease in the melting point of the core material, and its corrosion resistance can be easily improved by adjusting the potential of the core material.
[0063] In the aluminum alloy brazing board of the present invention, the core material may also contain Zn.
[0064] When the core material contains Zn, the Zn content in the core material is preferably 3.00% by mass or less, more preferably 0.50 to 2.50% by mass, and even more preferably 1.00 to 2.00% by mass.
[0065] By keeping the Zn content in the core material within the above-mentioned range, the natural potential of the core material is made low, which makes it easier for the core material to function as a sacrificial anode for a long time.
[0066] In the aluminum alloy brazing board of the present invention, the core material may also contain Ti.
[0067] When the core material contains Ti, the Ti content in the core material is preferably 0.20% by mass or less, more preferably 0.05 to 0.20% by mass, and even more preferably 0.05 to 0.18% by mass.
[0068] By keeping the Ti content in the core material within the above-mentioned range, the corrosion of the core material proceeds in a layered manner, which can easily suppress corrosion in the depth direction.
[0069] In the aluminum alloy brazing board of the present invention, the core material may also contain Zr.
[0070] When the core material contains Zr, the Zr content in the core material is preferably 0.50% by mass or less, more preferably 0.05% to 0.30% by mass, and even more preferably 0.10% to 0.20% by mass.
[0071] By keeping the Zr content in the core material within the above-mentioned range, the corrosion of the core material proceeds in a layered manner, which can easily suppress corrosion in the depth direction.
[0072] In the aluminum alloy brazing board of the present invention, the core material may also contain Cr.
[0073] When the core material contains Cr, the Cr content in the core material is preferably 0.50% by mass or less, more preferably 0.05 to 0.30% by mass, and even more preferably 0.10 to 0.20% by mass.
[0074] By keeping the Cr content in the core material within the above-mentioned range, the corrosion of the core material proceeds in a layered manner, which can easily suppress corrosion in the depth direction.
[0075] In the aluminum alloy brazing board of the present invention, the core material may also contain V.
[0076] When the core material contains V, the V content in the core material is preferably 0.50% by mass or less, more preferably 0.05 to 0.30% by mass, and even more preferably 0.10 to 0.20% by mass.
[0077] By keeping the V content in the core material within the above-mentioned range, the corrosion of the core material proceeds in a layered manner, which can easily suppress corrosion in the depth direction.
[0078] In this application, the content of each component constituting the core material refers to the value measured by an emission spectroscopy analyzer.
[0079] In the aluminum alloy brazing board of the present invention, a brazing filler metal is coated on one or both sides of the core material. The brazing filler metal comprises an aluminum alloy containing 6.00 to 13.00% by mass of Si and Mg content limited to less than 0.05% by mass, with the balance comprising aluminum and unavoidable impurities.
[0080] In the aluminum alloy brazing board of the present invention, the brazing filler metal contains Si.
[0081] The Si contained in the brazing filler metal lowers the melting point of Al and improves its fluidity, thus enabling the brazing filler to perform its function.
[0082] The Si content in the solder is 6.00–13.00% by mass, preferably 6.70–12.80% by mass, and more preferably 9.00–12.50% by mass.
[0083] By keeping the Si content in the solder within the above range, sufficient fluidity can be achieved, and erosion of the core material or other joined parts can be suppressed.
[0084] In the aluminum alloy brazing board of the present invention, the Mg content in the brazing filler metal is limited to less than 0.05% by mass.
[0085] The Mg contained in the brazing filler metal can easily embrittle and destroy the aluminum oxide film covering the surface of the filler metal during the hard brazing heating process. However, in this application, the Mg content in the filler metal is limited in order to suppress the formation of the MgO film on the surface of the filler metal.
[0086] The Mg content in the brazing filler metal is less than 0.05% by mass (more than 0.00% by mass and less than 0.05% by mass), preferably 0.00 to 0.04% by mass, and more preferably 0.00 to 0.02% by mass.
[0087] By making the Mg content in the brazing filler metal less than 0.05% by mass, the formation of MgO on the surface of the brazing filler metal can be suppressed, and a sufficient amount of Mg can diffuse and dissolve from the core material into the brazing filler metal during hard brazing, so that the aluminum oxide film on the surface of the brazing filler metal becomes embrittled.
[0088] In the aluminum alloy brazing board of the present invention, the brazing filler metal may also contain Bi.
[0089] The Bi content in the brazing filler metal is preferably 1.00% by mass or less, more preferably 0.005 to 1.00% by mass, even more preferably 0.01 to 0.40% by mass, even more preferably 0.010 to 0.20% by mass, and even more preferably 0.01 to 0.10% by mass.
[0090] By keeping the Bi content in the drill bit within the above range, the surface tension of the drill bit is reduced, which makes it easier to improve the fluidity of the drill bit.
[0091] In the aluminum alloy brazing board of the present invention, the brazing filler metal may also contain one or both elements selected from Sr and Na.
[0092] The Sr content in the brazing filler metal is preferably 0.100% by mass or less, more preferably 0.070% by mass or less, and even more preferably 0.050% by mass or less.
[0093] There is no particular limit to the lower limit of Sr content in the solder, but it is preferably 0.003% by mass or more.
[0094] The Na content in the brazing filler metal is preferably 0.300% by mass or less, more preferably 0.200% by mass or less, and even more preferably 0.100% by mass or less.
[0095] There is no particular limit to the lower limit of Na content in the solder, but it is preferably 0.002% by mass or more.
[0096] By keeping the contents of Sr and Na within the aforementioned ranges, the microstructure of the solidified brazed joint can be refined, thereby improving the joint strength.
[0097] The total content of Sr and Na in the brazing filler metal is preferably 0.002 to 0.600% by mass, more preferably 0.003 to 0.400% by mass, and even more preferably 0.005 to 0.200% by mass.
[0098] In this application, the content of each component constituting the solder can be measured by an emission spectroscopy analyzer.
[0099] In the aluminum alloy brazing board of the present invention, the Mg integral value from the surface of the brazing filler metal to a depth of 30 nm is 150 atm% × nm or less, preferably 110 atm% × nm or less, and more preferably 70 atm% × nm or less.
[0100] In the aluminum alloy brazing board of the present invention, by making the Mg integral value from the surface of the brazing filler metal to a depth of 30 nm less than 150 atm% × nm, the thickness of the MgO film on the surface of the brazing filler metal is controlled to a predetermined thickness. During brazing, the MgO film is easily broken, and the molten brazing filler metal wets and spreads on the surface, thus easily obtaining good brazing properties.
[0101] In this application, the Mg integral value from the surface of the solder to a depth of 30 nm refers to the cumulative value of the Mg concentration up to a depth of 30 nm when the solder surface is sputtered with argon ions using an X-ray photoelectron spectroscopy (XPS) device.
[0102] The Mg concentration per 1 nm depth was determined by the sputtering rate (sputtering depth / sputtering time) and sputtering time measured by XPS. The sputtering rate (sputtering depth / sputtering time) was calculated based on the time taken to measure the O concentration while sputtering a SiO2 film of known thickness until the O concentration measurement reached 0.
[0103] Based on the inventors' research, the formation and growth process of MgO film during brazing heating has been studied in depth, and the following insights have been obtained.
[0104] That is, if a brazing board made by coating a core material containing a predetermined amount of Mg with a solder containing a limited proportion of Mg is subjected to brazing heating, Mg will diffuse from the core material to the solder and react with oxygen in the atmosphere to form MgO when it reaches the surface of the solder from the inside of the solder.
[0105] In this way, the concentration of Mg metal near the surface of the solder decreases while the concentration difference between the Mg metal near the surface and the interior of the solder increases, making it easier for Mg metal inside the solder to move towards the surface of the solder.
[0106] When metallic Mg reaches the vicinity of the solder surface, it will further react with oxygen in the atmosphere to form MgO, and a Mg concentration layer will be formed in the outermost layer from the solder surface to a depth of 30 nm.
[0107] Figure 1 (a) is a graph showing the relationship between Mg concentration and the distance (μm) from the surface of the solder that constitutes the above-mentioned aluminum alloy brazing board. Figure 1 (b) is Figure 1 A magnified view of the portion shown by the dashed line in (a).
[0108] It is known that even if... Figure 1 As shown in (a), aluminum alloy brazing boards with a limited Mg content near the surface (at a distance of 0 μm from the material surface) will also... Figure 1 As shown in (b), a Mg concentration layer with a high Mg concentration is formed in the outermost layer from the surface of the solder to a depth of 30 nm.
[0109] The inventors have discovered that by using an aluminum alloy brazing board as described below, the thickness of the MgO film on the surface of the brazing filler metal during brazing can be controlled, and the alumina film and MgO film can be easily embrittled during brazing, thus enabling better brazing. This invention is thus completed. The aluminum alloy brazing board is a brazing board formed by coating a core material containing a predetermined amount of Mg with a brazing filler metal containing a limited proportion of Mg. The Mg integral value in the Mg concentration layer on the surface of the brazing filler metal is pre-controlled to be below a predetermined value.
[0110] The aluminum alloy brazing board of the present invention has a core material and a brazing filler metal covering one or both sides of the core material.
[0111] As an aluminum alloy brazing board of the present invention, examples include (1) a two-layer material form in which brazing filler metal is coated only on one side of the core material (core material / brazing filler metal), (2) a three-layer material form in which brazing filler metal is coated on both sides of the core material (brazing filler metal / core material / brazing filler metal), and (3) a three-layer material form in which brazing filler metal is coated on one side of the core material and sacrificial anode material is coated on the other side (brazing filler metal / core material / sacrificial anode material).
[0112] In the aluminum alloy brazing board of the present invention, the coverage rate of the brazing filler metal covering one or both sides of the core material (the ratio of the thickness of the brazing filler metal to the thickness of the aluminum alloy brazing board) is preferably 3 to 30%, more preferably 5 to 25%, and even more preferably 7 to 20%.
[0113] In the case where the aluminum alloy brazing board of the present invention adopts the form of a three-layer material in which the core material is covered with brazing filler metal on both sides, the composition and coverage of the brazing filler metal formed on each of the two sides of the core material can be the same or different.
[0114] In the case where the aluminum alloy brazing board of the present invention is in the form of a three-layer material (3) with brazing filler metal on one side of the core material and sacrificial anode material on the other side, the sacrificial anode material preferably contains aluminum or an aluminum alloy containing less than 8.00% by mass of Zn and the balance contains aluminum and unavoidable impurities.
[0115] There is no particular limitation on the purity of the aluminum constituting the above-mentioned sacrificial anode material, but it is preferably 99.0% by mass or more, and more preferably 99.5% by mass or more.
[0116] The aluminum alloy of the sacrificial anode material preferably contains Zn. The Zn in the sacrificial anode material has the effect of creating a low potential, thereby achieving a sacrificial corrosion protection effect by forming a potential difference between the sacrificial anode material and the core material. The Zn content in the sacrificial anode material is preferably 8.00% by mass or less, more preferably 3.00% by mass or less.
[0117] In the aluminum alloy brazing board of the present invention, the sacrificial anode material may also contain Fe.
[0118] When the sacrificial anode material contains Fe, the Fe content in the sacrificial anode material is preferably 1.00% by mass or less, more preferably 0.05 to 0.80% by mass, and even more preferably 0.100 to 0.700% by mass.
[0119] By keeping the Fe content in the sacrificial anode material within the above range, it is easier to improve the strength and increase the deformation resistance during hot rolling, thereby reducing the difference in deformation resistance between the anode material and the core material.
[0120] In the aluminum alloy brazing board of the present invention, the sacrificial anode material may also contain Mn.
[0121] When the sacrificial anode material contains Mn, the Mn content in the sacrificial anode material is preferably 1.80% by mass or less, more preferably 0.10 to 1.50% by mass, and even more preferably 0.20 to 1.20% by mass.
[0122] By keeping the Mn content in the sacrificial anode material within the above-mentioned range, the grain size of the sacrificial anode material formed by recrystallization during brazing can be adjusted.
[0123] In the aluminum alloy brazing board of the present invention, the sacrificial anode material may also contain Mg.
[0124] When the sacrificial anode material contains Mg, the Mg content in the sacrificial anode material is preferably 1.00% by mass or less, more preferably 0.05 to 1.00% by mass, and even more preferably 0.10 to 0.80% by mass.
[0125] By keeping the Mg content in the sacrificial anode material within the above-mentioned range, the strength of the sacrificial anode material can be easily improved.
[0126] In this application, the content of each component constituting the sacrificial anode material refers to the value measured by an emission spectrometer (XPS).
[0127] In the aluminum alloy brazing board of the present invention, the coverage ratio of the sacrificial anode material (the ratio of the thickness of the sacrificial anode material to the thickness of the aluminum alloy brazing board) is preferably 3 to 30%, more preferably 5 to 25%, and even more preferably 7 to 20%.
[0128] The aluminum alloy brazed plate of the present invention can be used as a fin that serves as a heat transfer medium in a heat exchanger, a tube that serves as a flow path structure material for the flow of refrigerant, etc., and a plate that is joined with a tube to form a structure for a heat exchanger.
[0129] When the aluminum alloy brazing plate of the present invention is used as a fin material, the thickness of the brazing plate is preferably about 0.04 to 0.20 mm.
[0130] When the aluminum alloy brazing plate of the present invention is used for pipes, the thickness of the brazing plate is preferably about 0.15 to 0.50 mm.
[0131] When the aluminum alloy brazing plate of the present invention is used in a sheet material, the thickness of the brazing plate is preferably about 0.80 to 5.00 mm.
[0132] For the aluminum alloy brazing board of the present invention, the surface of its brazing filler metal can also be etched by acid.
[0133] The above etching process can pre-embrittle or remove the aluminum oxide film and MgO film formed on the surface.
[0134] The details of the above etching process are described below.
[0135] According to the present invention, a brazing board with excellent brazing properties can be provided when brazing aluminum materials in an inactive gas atmosphere such as nitrogen without the use of flux.
[0136] Next, a method for manufacturing the aluminum alloy brazing board of the present invention will be described.
[0137] The manufacturing method of the present invention is a method for manufacturing the aluminum alloy brazing board of the present invention, characterized in that...
[0138] An aluminum alloy brazing board is manufactured by subjecting a laminate consisting of a core material ingot and a brazing filler ingot on one or both sides of the core material ingot to at least hot working, cold working, and at least one annealing treatment selected from at least one intermediate annealing between cold working rolling passes and a final annealing after the last cold working pass.
[0139] So that the value of the diffusion amount D, expressed by the following equation (I), becomes 7.0 × 10⁻⁶. -10 m 2 The heating process for one or more annealing treatments, selected from the intermediate annealing between the cold rolling passes and the final annealing after the last cold working pass, is performed in the following manner.
[0140] D=ΣD0·exp(-Q / (RTn))·Δtn (I)
[0141] (In the formula, Tn is the heating temperature (K) in each minute time interval when the total heating time (seconds) of the intermediate annealing and final annealing is divided into minute time intervals Δtn (seconds), D0 = 1.24 × 10 -4 (m 2 / s), Q=130(kJ / mol), R=8.3145(J / (mol·K))).
[0142] In the method for manufacturing the aluminum alloy brazing board of the present invention, firstly, an aluminum alloy having a desired composition for the core material, the brazing filler metal, and the sacrificial anode material (provided as needed) is melted and cast separately to produce ingots for the core material, the brazing filler metal, and the sacrificial anode material (provided as needed). These melting and casting methods are not particularly limited, and conventional methods can be used.
[0143] Next, the core material ingot, the brazing filler metal ingot, and the sacrificial anode material ingot (if required) are preferably subjected to appropriate homogenization treatment. The preferred temperature range for homogenization treatment is 400–600°C, and the homogenization treatment time is 2–20 hours.
[0144] Next, after milling or hot rolling the core material ingot, the brazing filler ingot, and the sacrificial anode material ingot (as needed) to a predetermined thickness, the ingots are stacked in a predetermined order to form a laminate.
[0145] The aforementioned core material ingot, brazing filler metal ingot, and sacrificial anode material ingot, which are provided as needed, each have a composition corresponding to the composition of the core material, brazing filler metal, and sacrificial anode material that constitute the desired aluminum alloy brazing board.
[0146] In the method for manufacturing the aluminum alloy brazing plate of the present invention, the above-mentioned laminate is subjected to at least one heat treatment, including hot working, cold working, and at least one intermediate annealing between the rolling passes of cold working and the final annealing after the last cold working pass.
[0147] In hot working, a stack of predetermined ingots, arranged in a predetermined sequence, is hot rolled at 400–500°C. During hot rolling, for example, the material is rolled until it reaches a plate thickness of 2–8 mm.
[0148] In cold working, the hot-rolled material obtained through hot working is cold-rolled. In cold working, cold rolling is performed in multiple passes.
[0149] In cold working, one or more intermediate annealings between cold rolling passes are preferably performed at a heating temperature of 200 to 500°C, and more preferably at a heating temperature of 250 to 400°C.
[0150] In intermediate annealing, the temperature is raised to the intermediate annealing temperature. Alternatively, cooling can begin rapidly after reaching the intermediate annealing temperature, or cooling can begin after holding the intermediate annealing temperature for a certain period of time. The holding time at the intermediate annealing temperature is 0 to 10 hours, preferably 1 to 5 hours.
[0151] After cold rolling, the resulting cold-rolled material is subjected to appropriate final annealing.
[0152] The final annealing is preferably carried out at a heating temperature of 300 to 500°C, and more preferably at a heating temperature of 350 to 450°C.
[0153] In the final annealing, the temperature is raised to the final annealing temperature. This can be done by rapidly cooling after reaching the final annealing temperature, or by holding the temperature at the final annealing temperature for a certain period of time before cooling begins. The holding time at the final annealing temperature is 0 to 10 hours, preferably 1 to 5 hours.
[0154] There are no particular limitations on the atmosphere during the intermediate annealing and the final annealing, but it is preferable to carry out the process in an atmosphere with a lower oxygen concentration than that in the atmosphere. By heating in an atmosphere with a lower oxygen concentration than that in the atmosphere, the growth of oxide film on the surface of the solder can be suppressed.
[0155] In the manufacturing method of the aluminum alloy brazing board of the present invention, the intermediate annealing or final annealing is preferably performed when the brazing filler metal is rolled into an ingot with a thickness of 10 μm to 50 μm, and more preferably when it is rolled into an ingot with a thickness of 20 μm to 50 μm.
[0156] By controlling the thickness of the solder ingot during intermediate or final annealing within the aforementioned range, the Mg concentration diffusing from the core material ingot to the surface of the solder ingot can be reduced, thereby inhibiting the formation and growth of the MgO film and making it easier to achieve the desired brazing characteristics.
[0157] In the method for manufacturing the aluminum alloy brazing board of the present invention, the value of the diffusion amount D, expressed by the following formula (I), is made to be 7.0 × 10⁻⁶. -10 m 2 The heating process in one or more annealing treatments selected from the intermediate annealing between the aforementioned cold rolling passes and the final annealing after the last cold working pass is performed in the following manner.
[0158] D=ΣD0·exp(-Q / (RTn))·Δtn (I)
[0159] (In the formula, Tn is the heating temperature (K) in each minute time interval when the total heating time (seconds) of the intermediate annealing and final annealing is divided into minute time intervals Δtn (seconds), D0 = 1.24 × 10 -4 (m 2 / s), Q=130(kJ / mol), R=8.3145(J / (mol·K))).
[0160] In the method for manufacturing the aluminum alloy brazed plate of the present invention, the heating in the intermediate annealing between the cold rolling passes and the heating in the final annealing after the last cold working pass are used to make the value of the diffusion amount D reach 7.0 × 10⁻⁶. -10 m 2 The following method is preferred to achieve a diffusion amount D of 5.0 × 10⁻⁶. -10 m2 The following method is preferred to make the value of the diffusion amount D 2.0 × 10⁻⁶. -10 m 2 The following method will be used.
[0161] There is no particular limitation on the lower limit of the diffusion amount D mentioned above, but the diffusion amount D is usually 1.0 × 10⁻⁶. -16 m 2 above.
[0162] By making the value of the diffusion amount D above 7.0 × 10 -10 m 2 The following method of heating during intermediate annealing between the aforementioned cold rolling passes and heating during final annealing after the final cold working pass can limit the amount of Mg diffusion from the core material ingot to the surface of the brazing filler metal ingot.
[0163] In the manufacturing method of the aluminum alloy brazing plate of the present invention, heating is performed during the intermediate annealing between the above-mentioned cold rolling passes and the final annealing after the last cold working pass, so that the Mg contained in the core material diffuses toward the surface of the brazing filler metal. However, by controlling the temperature and time during the intermediate annealing and the final annealing, the diffusion amount D calculated by formula (I) becomes 7.0 × 10⁻⁶. -10 m 2 The following allows for easy control of its diffusion rate.
[0164] According to conventional methods, it is believed that if the temperature ultimately reached through heat treatment and the time it is held at that temperature are controlled, a suitable diffusion effect can be obtained.
[0165] However, as described above, the Mg integral value of the aluminum alloy brazed board obtained by the manufacturing method of the present invention, from the surface of the solder to a depth of 30 nm, is controlled to be below 150 atm% × nm. In order to control this Mg integral value to an appropriate value, it is necessary to appropriately control the total amount of heat input during the entire process of intermediate annealing and final annealing. In order to satisfy this necessary condition, it is necessary to make the diffusion amount D calculated by the above formula (I) 7.0 × 10⁻⁶. -10 m 2 The preferred value is 5.0 × 10⁻⁶. -10 m 2 Hereinafter, 2.0 × 10 is preferred. -10 m 2 The following methods can be used for control.
[0166] In the method for manufacturing the aluminum alloy brazing board of the present invention, acid may be used to etch the surface of the brazing board as needed.
[0167] Etching can embrittle or remove aluminum oxide and MgO films formed during heating in hot rolling, heating between cold rolling passes, and heating after the final pass.
[0168] The etching process can be performed from the time of hot rolling until the time of brazing with a brazing plate, and is not particularly limited.
[0169] For example, etching can be performed on hot-rolled cladding sheets, or on cladding sheets that are cold-rolled. Alternatively, etching can be performed after intermediate annealing or after final annealing.
[0170] Alternatively, after the final annealing is completed, the brazing board can be stored in a state with an oxide film, and an etching process can be performed before brazing.
[0171] If the oxide film is embrittled or removed during brazing, the brazing performance of the brazing board can be improved.
[0172] As mentioned above, by performing an etching process, the MgO film formed on the surface of the solder can be embrittled or removed, thereby reducing the Mg concentration on the surface of the solder.
[0173] For example, in thin-plate materials such as fin materials used in automotive heat exchangers, there is sometimes an etching process before the annealing process due to equipment limitations. In such cases, etching can reduce the Mg concentration on the solder surface, and by optimizing the processing conditions of the subsequent annealing process, the oxide film can be made embrittled, thus improving brazing properties.
[0174] As acids for etching processes of brazed boards, aqueous solutions of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, hydrofluoric acid, etc., can be used, for example. These acids can be used alone or in combination of two or more. From the viewpoint of more efficiently removing oxide films, it is preferable to use an aqueous solution containing hydrofluoric acid and acids other than hydrofluoric acid, and more preferably an aqueous solution containing a mixture of hydrofluoric acid and sulfuric acid or a mixture of hydrofluoric acid and nitric acid.
[0175] The etching amount during etching is preferably 0.05–2.00 g / m. 2 By setting the etching amount to 0.05 g / m 2 The above, more preferably 0.10 g / m 2 In this way, the oxide film on the surface of the brazing board can be completely removed, which can further improve the brazing performance.
[0176] From the perspective of improving the solderability of brazed boards, there is no upper limit to the amount of etching.
[0177] However, when the etching amount becomes excessive, it may be difficult to achieve the desired improvement in solderability that matches the processing time. By setting the etching amount to 2.00 g / m... 2 The following is more preferably 0.50 g / m 2 The following methods can easily avoid this problem.
[0178] In the method for manufacturing the aluminum alloy brazing board of the present invention, the aluminum alloy brazing board can be obtained in this way.
[0179] The details of the obtained aluminum alloy brazing board have been described in detail in the description of the aluminum alloy brazing board of the present invention.
[0180] According to the present invention, it is possible to easily manufacture a brazed board with excellent brazing properties by brazing aluminum materials in an inactive gas atmosphere such as nitrogen without the use of flux.
[0181] The present invention is illustrated below with examples, but the present invention is not limited to the examples shown below.
[0182] Example
[0183] (Example 1)
[0184] (1) Through continuous casting, core material ingots and multiple brazing filler ingots with the chemical composition shown in Table 1 were produced respectively.
[0185] Next, after homogenizing the core material ingot, face milling is performed to achieve a predetermined thickness for the core material ingot. Then, multiple solder ingots are hot-rolled separately to achieve a predetermined thickness for the solder ingot.
[0186] The core material ingot and multiple solder ingots obtained in this way are stacked in the order of solder 1 ingot / core material ingot / solder 2 ingot to obtain a three-layer stack with solder 1 ingot and solder 2 ingot stacked on each of the two sides of the core material ingot.
[0187] By hot rolling the obtained laminate, the core material ingot and the brazing ingot are joined together, thereby producing a cladding material with a plate thickness of 2.6 mm.
[0188] (2) The coating material obtained from (1) was cold rolled to obtain a cold-rolled material with a thickness of 0.17 mm.
[0189] Next, for the obtained cold-rolled material, the value of the diffusion amount D, expressed by the following formula (I), is made to be 1.0 × 10⁻⁶. -10 m 2 In this manner, under atmospheric conditions, intermediate annealing was carried out by controlling the heating temperature and heating time simultaneously.
[0190] D=ΣD0·exp(-Q / (RTn))·Δtn (I)
[0191] (In the formula, Tn is the heating temperature (K) in each minute time interval when the total heating time (seconds) of the intermediate annealing and final annealing is divided into minute time intervals Δtn (seconds), D0 = 1.24 × 10 -4 (m 2 / s), Q=130(kJ / mol), R=8.3145(J / (mol·K))).
[0192] The intermediate annealed material was subjected to cold rolling to obtain an experimental material of aluminum alloy brazing board with a thickness of 0.10 mm. The material consists of a three-layer structure of brazing filler metal 1 / core material / brazing filler metal 2, and the brazing filler metal coverage on the two sides of the core material is 12.6% (brazing filler metal 1) and 11.3% (brazing filler metal 2).
[0193] The preparation conditions for the above-mentioned test materials are shown in Table 3.
[0194] The Mg integral value of the obtained test material from the surface of solder 1 to a depth of 30 nm was measured using an X-ray photoelectron spectroscopy analyzer (XPS, ULVAC-PHI PHI 5000 VersaProbeIII). The results are shown in Table 4.
[0195] In addition, the thickness of the oxide film on the surface of the solder 1 of the test materials was measured using XPS (X-ray photoelectron spectroscopy). In this case, for the solder surface of each test material, the O (oxygen) in the depth direction was measured, and its half-width was set as the thickness of the oxide film. The results are shown in Table 4.
[0196] <Evaluation of solderability>
[0197] Using the obtained test materials, a micro-core test specimen simulating the core of a corrugated finned heat exchanger was fabricated by the following method, and the brazing performance was evaluated based on the fin adhesion rate.
[0198] In this evaluation, firstly, such as Figure 2 As shown, a microcore test specimen was fabricated, which has: a corrugated fin 1 comprising a brazed plate having solder on both sides made of the test material obtained in the above embodiments or comparative examples; and two flat plates 2, 2 that hold the corrugated fin 1.
[0199] Specifically, after the obtained test material was cut to a predetermined size, it was corrugated to obtain a corrugated fin 1-1 with a length of 35 mm, a height of 3 mm, and a top spacing of 4.5 mm.
[0200] In addition, two flat plates 1-2 were obtained by cutting out JIS A3003 alloy plates with a length of 35mm, a width of 30mm, and a thickness of 1.0mm.
[0201] After degreasing the corrugated fin 1 and the two plates 2, 2 with acetone, the corrugated fin 1 is clamped by the two plates 2, 2 to form an assembly.
[0202] The resulting assembly was heated to 600°C in an inert gas atmosphere under heating conditions that required 3 minutes to reach 400°C from 150°C and 5 minutes to reach 600°C from 400°C.
[0203] Next, the solder was melted by holding the plate at 600°C for 3 minutes, and the plate and the corrugated fin containing the core material were brazed. The brazing atmosphere was -60°C with an oxygen concentration of 1 ppm.
[0204] The corrugated fin 1 is removed from the micro core test piece after the above heat treatment. Based on the weld marks present on the two flat plates 2, 2, the bonding rate is calculated by the following method.
[0205] First, for the weld marks present on the two plates 2, 2 respectively, their lengths in the width direction d of each plate 2 are measured, and their total length L1 is calculated. In addition, the total length L0 of each weld mark in the width direction d of the plate 2 is calculated assuming that the two plates 2, 2 and the corrugated fin 1 are fully joined. Then, the ratio of the length L1 to the length L0 is calculated as the joining rate (%).
[0206] Furthermore, the length L0 can be calculated, for example, by multiplying the width of the corrugated fin 1 (the length of the plate 2 in the width direction) by the number of tops of the corrugated fins 1-2.
[0207] However, in this embodiment, in order to eliminate the deviation in adhesion rate caused by poor assembly, the two ends in the width direction ( Figure 2 In the example shown, the two ends indicated by the dashed lines in the figure are excluded when calculating the bonding rate.
[0208] Based on the obtained bonding rate, a bonding rate of 60% or higher was judged as good solderability (〇), and a bonding rate of less than 60% was judged as poor solderability (×), thus evaluating the solderability. The results are shown in Table 4.
[0209] (Example 2)
[0210] To make the value of the diffusion amount D 2.7 × 10⁻⁶ -10 m 2The heating temperature and heating time during intermediate annealing were controlled by a method similar to that in Example 1. Otherwise, the process was carried out in the same way, and an experimental material of aluminum alloy hard brazing board with a thickness of 0.10 mm was obtained, which consists of a three-layer structure of brazing filler metal 1 / core material / brazing filler metal 2 and has brazing filler metal coverage of 12.6% (brazing filler metal 1) and 11.3% (brazing filler metal 2) on the two sides of the core material.
[0211] The obtained test materials were evaluated in the same manner as in Example 1. The results are shown in Table 4.
[0212] (Example 3)
[0213] To make the value of diffusion amount D 6.7 × 10 -10 m 2 The heating temperature and heating time during intermediate annealing were controlled by a method similar to that in Example 1. Otherwise, the process was carried out in the same way, and an experimental material of aluminum alloy hard brazing board with a thickness of 0.10 mm was obtained, which consists of a three-layer structure of brazing filler metal 1 / core material / brazing filler metal 2 and has brazing filler metal coverage of 12.6% (brazing filler metal 1) and 11.3% (brazing filler metal 2) on the two sides of the core material.
[0214] The obtained test materials were evaluated in the same manner as in Example 1. The results are shown in Table 4.
[0215] (Comparative Example 1)
[0216] To make the value of diffusion amount D 13.5 × 10 -10 m 2 The heating temperature and heating time during intermediate annealing were controlled by a method similar to that in Example 1. Otherwise, the process was carried out in the same way, and an experimental material of aluminum alloy hard brazing board with a thickness of 0.10 mm was obtained, which consists of a three-layer structure of brazing filler metal 1 / core material / brazing filler metal 2 and has brazing filler metal coverage of 12.6% (brazing filler metal 1) and 11.3% (brazing filler metal 2) on the two sides of the core material.
[0217] The obtained test materials were evaluated in the same manner as in Example 1. The results are shown in Table 4.
[0218] (Example 4)
[0219] (1) A covering material with a thickness of 2.6 mm was prepared using the same method as in Example 1 (1).
[0220] (2) The coating material obtained from (1) is cold rolled to obtain a cold-rolled material with a thickness of 0.30 mm. The cold-rolled material is then etched using an etching solution at 70°C (containing 0.1% hydrofluoric acid and 1.0% sulfuric acid).
[0221] Next, the etched material was further subjected to cold rolling to obtain a cold-rolled material with a thickness of 0.17 mm.
[0222] Subsequently, for the obtained cold-rolled material, the value of the diffusion amount D, expressed by the following formula (I), is made to be 1.0 × 10⁻⁶. -10 m 2 In this manner, intermediate annealing was carried out under an atmosphere where the oxygen concentration was controlled to below 0.2% by volume, with simultaneous control of heating temperature and heating time.
[0223] D=∑D0·exp(-Q / (RTn))·Δtn (I)
[0224] (In the formula, Tn is the heating temperature (K) in each minute time interval when the total heating time (seconds) of the intermediate annealing and final annealing is divided into minute time intervals Δtn (seconds), D0 = 1.24 × 10 -4 (m 2 / s), Q=130(kJ / mol), R=8.3145(J / (mol·K))).
[0225] The intermediate annealed material was subjected to cold rolling to obtain an experimental material of aluminum alloy brazing board with a thickness of 0.10 mm. The material consists of a three-layer structure of brazing filler metal 1 / core material / brazing filler metal 2, and the brazing filler metal coverage on the two sides of the core material is 12.6% (brazing filler metal 1) and 11.3% (brazing filler metal 2).
[0226] The obtained test materials were evaluated in the same manner as in Example 1. The results are shown in Table 4.
[0227] (Example 5)
[0228] Using core material ingots, solder 1 ingots, and solder 2 ingots with the chemical compositions shown in Table 2, produced by continuous casting, and changing the atmosphere during intermediate annealing to an atmosphere where the oxygen concentration is controlled to be below 0.2% by volume, the same process as in Example 1 was performed to obtain an aluminum alloy brazing board with a thickness of 0.10 mm, consisting of a three-layer structure of solder 1 / core material / solder 2, with solder coverage of 11.9% (solder 1) and 12.1% (solder 2) on the two sides of the core material.
[0229] The obtained test materials were evaluated in the same manner as in Example 1. The results are shown in Table 4.
[0230] [Table 1]
[0231] <Examples 1-4, Comparative Example 1>
[0232]
[0233] (Unit: mass%)
[0234] *: In the table, "Bal." refers to the margin.
[0235] [Table 2]
[0236] <Example 5>
[0237]
[0238] (Unit: mass%)
[0239] *: In the table, "Bal." refers to the margin.
[0240] [Table 3]
[0241]
[0242] *: In the table, "control" means controlling the oxygen concentration to below 0.2% by volume.
[0243] [Table 4]
[0244]
[0245] As shown in Table 4, in the test materials of the aluminum alloy brazing boards obtained by Examples 1 to 5, the core material contains an aluminum alloy containing 0.10 to 0.50% by mass of Mg and the balance contains aluminum and unavoidable impurities. The solder contains an aluminum alloy containing 6.00 to 13.00% by mass of Si and the Mg content is limited to less than 0.05% by mass, the balance contains aluminum and unavoidable impurities. Furthermore, the Mg integral value from the solder surface to a depth of 30 nm is less than 150 atm% × nm. Therefore, all brazing properties were evaluated as "0", indicating good brazing properties (jointness).
[0246] On the other hand, as shown in Table 4, the Mg integral value of the test material of the aluminum alloy brazed board obtained in Comparative Example 1 from the surface of the solder to a depth of 30 nm is relatively high, which is 195 atm% × nm. Therefore, it is rated as "×" when evaluating brazability, indicating poor brazability (jointness).
[0247] Industrial availability
[0248] According to the present invention, a brazing board with excellent brazing properties when brazing aluminum materials in an inactive gas atmosphere such as nitrogen without the use of flux, and a method thereof are provided.
Claims
1. An aluminum alloy brazing plate for brazing in an inactive gas atmosphere, characterized in that, The aluminum alloy brazing board has a core material and a brazing filler metal covering one or both sides of the core material. The core material comprises an aluminum alloy containing 0.10 to 0.50% by mass of Mg, with the balance consisting of aluminum and unavoidable impurities. The brazing filler metal comprises an aluminum alloy containing 6.00 to 13.00% by mass of Si, with the Mg content limited to less than 0.05% by mass, and the balance consisting of aluminum and unavoidable impurities. The Mg integral value from the surface of the solder up to a depth of 30 nm is less than 150 atm% × nm.
2. The aluminum alloy brazing plate according to claim 1, characterized in that, The brazing filler metal also contains 0.005 to 1.00% by mass of Bi.
3. The aluminum alloy brazing plate according to claim 1, characterized in that, The core material also contains 0.05-0.70% by mass of Fe, 0.10-0.70% by mass of Si, 0.40-1.60% by mass of Mn, and 0.05-0.50% by mass of Cu.
4. The aluminum alloy brazing plate according to claim 2, characterized in that, The core material also contains 0.05-0.70% by mass of Fe, 0.10-0.70% by mass of Si, 0.40-1.60% by mass of Mn, and 0.05-0.50% by mass of Cu.
5. The aluminum alloy brazing plate according to any one of claims 1 to 4, characterized in that, The core material also contains 0.50 to 3.00% by mass of Zn.
6. The aluminum alloy brazing plate according to any one of claims 1 to 4, characterized in that, The surface of the aluminum alloy brazed plate was etched with acid.
7. The aluminum alloy brazing plate according to claim 5, characterized in that, The surface of the aluminum alloy brazed plate was etched with acid.
8. A method for manufacturing an aluminum alloy brazing board, comprising the method for manufacturing the aluminum alloy brazing board according to any one of claims 1 to 7, characterized in that, An aluminum alloy brazing board is manufactured by subjecting a laminate consisting of a core material ingot and a brazing filler ingot on one or both sides of the core material ingot to at least hot working, cold working, and at least one annealing treatment selected from at least one intermediate annealing between cold working rolling passes and a final annealing after the last cold working pass. So that the value of the diffusion amount D, expressed by the following equation (I), becomes 7.0 × 10⁻⁶. -10 m 2 The following method is used for heating during one or more annealing processes, selected from intermediate annealing between cold rolling passes and final annealing after the last cold working pass. D=ΣD0·exp(-Q / (RTn))·Δtn (I) In the formula, Tn is the heating temperature in each minute time interval when the total heating time of the intermediate annealing and final annealing is divided into minute time intervals Δtn, and D0 = 1.24 × 10 -4 Q=130, R=8.3145, where the total heating time and minute time Δtn are in seconds, the heating temperature is in K, and D0 is in meters. 2 / s, Q is in kJ / mol, and R is in J / (mol·K).
9. The method for manufacturing an aluminum alloy brazed plate according to claim 8, characterized in that, The intermediate annealing or final annealing is performed while the brazing filler metal is rolled into an ingot with a thickness of 10μm to 50μm.
Citation Information
Patent Citations
Flux-less brazing method of aluminum material, brazing sheet for flux-less brazing and method for manufacturing the same, brazing structure
JP2013215797A
Aluminum alloy brazing sheet, manufacturing method of the same, aluminum alloy sheet, and heat exchanger
JP2019069474A
Brazing sheet and method for producing same
CN112672845A